Antisocial behaviour genesis from the social information processing perspective - Valickas, Gintautas; Tarozienė, Viktorija (Psichologija, 2009)
Quite numerous research findings show that social information processing underlies different forms of prosocial and antisocial behaviour. Although most of data come from research of children of different age, interest in social information processing and behaviour in later periods of life markedly grows. More and more authors turn to the question of adult social information processing and antisocial behaviour, considering it as a promising field for criminal behaviour forecast and correction. Two aims ofthis paper are: 1) to describe the main developmental features of social information processing from early childhood to late adolescence and early adulthood; 2) to make assumptions on the connections between social information processing and the antisocial (criminal) behaviour of adults. In this article, we review findings of more than two last decades as it is the most intense period for the development of knowledge in this field. Analysis of the literature shows that patterns of social information processing of people with tendencies to prosocial and antisocial behaviour already differ in groups of children. These differences become more vivid in groups of adolescents as they tend to use antisocial thinking strategies more often and in more steps of information processing than younger children. We suppose that adults have similar but even more clear and vivid patterns of specific social information processing and behaviour than adolescents.Social knowledge of adults is more complex, abstract and differentiated to specific social situations in comparison with people of younger age. Moreover, their information processing is more rapid and complex as well as more tendentious and rigid. Automation of information processing might suspend the learning process and be a source of information processing mistakes in new social situations. We assume that adults, in comparison with children, must have a rather stable and effectively working social information processing directly linked to specific forms of prosocial or antisocial behaviour. We hypothesize that because of a longer antisocial (criminal) experience, some specific features of social knowledge and information processing might appear. Therefore, researches of social information processing that underlie specific forms of antisocial (criminal) behaviour seem to be most informative and useful in this field. Moreover, it is still very little known about the role of emotions in antisocial behaviour genesis. There is some eloquent data on their important impact on social information processing underlying antisocial behaviour, but we suppose that this impact might differ in particular stages of development.